NUMERICAL MODELLING TO DETERMINE THE IMPACT OF WIDTH:HEIGHT PILLAR RATIO TO UNDERGROUND COAL PILLAR STRENGTH - Hizkal, Muhammad
One of the coal underground mining methods risks is roof and pillar possibility to collapse. Pillar is the natural support to maintain the stability of underground mining entry. One of the main factors that determine the coal pillar strength is the pillar dimension or width:height ratio (W/H ratio). This study will analyze and compare stress-strain curves on each pillar ratio. The pillar will be modelled by numerical with implementing finite element method using Phase2 8.0 software. The variation of the ratio (W/H) is 0.5; 1.0; 1.5, 2.0; 2.5 and 3.0 with pillar height equal to 3 meters. Pillar model will be given pressure from 1 MPa to 6 MPa. Data plotted on the curve is the average of sigma 1 on half of the pillar height to yield stress value. Then, the vertical displacement on the pillar roof to yield strain value. The result of every pillar ratio on the curve shows that the bigger the pillar ratio, the bigger the pillar strength value. The linear equation of pillar strength is ????????= ????(????+????????????????). From the equation, pillar strength is proportional to pillar width but inversely proportional to pillar height.